Validation of a subclassification for high‐risk prostate cancer in a prospective cohort. Issue 10 (19th February 2020) - Butler, Santino S.; Dee, Edward C.; Lamba, Nayan; Sha, Sybil T.; Mahal, Brandon A.; Whitbeck, Amanda; Makkar, Rishi; Wangoe, Janet; Mouw, Kent W.; Nguyen, Paul L.; Muralidhar, Vinayak
Abstract : Background: A subgroup of men with favorable high‐risk prostate cancer (T1c with either a Gleason score of 4 + 4 = 8 and a prostate‐specific antigen [PSA] level <10 ng/mL or a Gleason score of 6 and a PSA level >20 ng/mL) has been associated with improved outcomes in comparison with other standard high‐risk patients. This study was designed to validate the prognostic utility of a subclassification for high‐risk disease with a prospectively collected data set. Methods: This study identified 3033 men from the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial who had been diagnosed from 1993 to 2001 with clinically localized prostate cancer—either intermediate‐risk disease (clinical stage T2b‐c, a Gleason score of 7, or a PSA level of 10 to 20 ng/mL) or high‐risk disease (clinical stage T3‐T4, a Gleason score of 8‐10, or a PSA level >20 ng/mL)—that was managed with radical prostatectomy or radiation therapy. Multivariable logistic regression was used to calculate adjusted odds ratios (aORs) for pathological T3 to T4 or N1 (pT3‐T4/pN1) disease. Fine and Gray competing risks regression was used to determine adjusted hazard ratios (aHRs) of prostate cancer–specific mortality (PCSM). Results: The median follow‐up was 5.7 years. Patients with favorable high‐risk disease had lower 8‐year PCSM in comparison with patients with standard high‐risk disease (2.2% vs 10.8%; aHR, 0.26; 95% confidence interval [CI], 0.09‐0.73; P = .01) but similar PCSM in comparison with patients with intermediate‐risk disease (2.2% vs 2.2%; aHR, 0.90; 95% CI, 0.32‐2.54; P = .84). Among those who underwent surgery, those with favorable high‐risk disease had lower odds of pT3‐T4/pN1 disease than those with standard high‐risk disease (46.2% vs 63.3%; aOR, 0.50; 95% CI, 0.27‐0.94; P = .03). Conclusions: This study validates the prognostic utility of a subclassification for high‐risk disease in a prospectively collected patient cohort. Patients with favorable high‐risk disease have PCSM similar to that of patients with intermediate‐risk disease and significantly better than that of patients with standard high‐risk disease. Future trials are needed to assess possible de‐intensification of therapy for favorable high‐risk disease. Abstract : The subgroup with favorable high‐risk prostate cancer has a risk of prostate cancer–specific mortality that is similar to the risk with intermediate‐risk disease and significantly better than the risk with other standard high‐risk disease. This study validates the prognostic utility of a subclassification for high‐risk disease in a prospectively collected patient cohort.